The Influence of Service Quality Based on the Servqual Theory on Community Satisfaction at the Patam Lestari Urban Village Office, Batam City - Ridho, Muhammad; Luthfi, Andi; Raymond, Raymond (Universitas Batam, 2025)
public service quality is a key factor in achieving community satisfaction. This research is to examine the impact of service quality on community satisfaction at the Patam Lestari village office in Batam City, using the servqual theory, which encompasses five Dimensions: tangibility, reliability, responsiveness, assurance, and empathy. The study used a quantitative technique using a survey design. The population included community members using public services at the Patam Lestari village office, with a sample of 99 respondents determined by the Slovin formula, with a 10% margin of error and selected via purposive sampling. Data were collected using a standardised questionnaire and analysed using multiple linear regression with SPSS version 19.0. The results demonstrate that all five dimensions of service quality exert both simultaneous and partial positive and substantial impacts on community satisfaction. The findings indicate that improving the quality of public services across all SERVQUAL characteristics may substantially increase community satisfaction. Consequently, government offices are urged to prioritise the ongoing enhancement of service quality to foster increased public trust and satisfaction.